Experimental infection of reindeer, sheep and goats with Elaphostrongylus spp. (Nematoda, Protostrongylidae) from moose and reindeer - Stéen, Margarets; Warsame, Ibrahim; Skorping, Arne (Rangifer, 1998)
Six reindeer (Rangifer tarandus), five sheep and six goats (Ovis ovis and Capra hircus) were experimentally infected with the nematode Elaphostrongylus alces. Additionally, one sheep was infected with E. rangiferi. Reindeer infected with E. alces showed no neurological signs. Sheep and goats infected with the same parasite also remained clinically healthy; however, the sheep infected with E. rangiferi showed severe neurological signs and became paralysed. Pathological lesions were minimal in reindeer and domestic ruminants infected with E. alces, but were prominent in the lamb infected with E. rangiferi. Our results indicate that keeping and transferring sheep and goats into ateas inhabited by moose, which is a natural host of E. alces may not harm the livestock, while keeping sheep in areas inhabited by reindeer infected with E. rangiferi may result in petiodic outbreaks of cerebrospinal elaphostrongylosis in sheep.